The Correlation between Lecturers’ Performance in Supervising Thesis and Thesis Quality in IAIN Palu - Erniati, Erniati; Yusuf, Khaeruddin; Hidayat, Andi Nurul (AT-TA'LIM, 2021)
This article aims to determine lecturers’ performance in supervising thesis with thesis quality of students of Faculty of Islamic Education and Teacher Training IAIN Palu. This is a quantitative study investigating 285 students of Faculty of Islamic Education and Teacher Training IAIN Palu. who had finished their thesis examinations in 2020 by using proportional sampling technique? The data collection techniques were surveys, observation, interview and documentation. The results showed that the performance of the lecturers in supervising the thesis was in good category with an average (mean) score of 79.79 and the quality of the thesis was in the good category with the average score (mean) of 81.16. There is a significant correlation between the performance of the lecturer in supervising the thesis and the thesis quality of the students.